(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
During recent years, the most effective and practical method for volcanic glass sourcing is the portable X-ray fluorescence. In spite of the reliability of this method and the growing demand, the Armenian obsidian sources have been analyzed by using the above-mentioned analytical method only in few studies. In order to make sourcing of any volcanic glass samples including archeological ones, a full database of so-called geological samples must be created first of all, which will include samples from all the sources of the region. Thus, this work is another attempt to study the Armenian obsidian sources, the ultimate goal of which is to create an analytical database of the sources using portable X-ray fluorescence method.